Utilization of maternal health services in rural Thawang, Rolpa district of Nepal: a community-based cross-sectional study - Jahirul Hushen; Arpaporn Powwattana; Chockchai Munsawaengsub; Sukhontha Siri (Journal of Health Research, 2022)
Purpose – This study aimed to identify the proportion and factors influencing the use of maternal health services (MHS) in rural Thawang, Rolpa, Nepal. Design/methodology/approach – This was a community-based cross-sectional study conducted among 417 mothers who had given birth in the previous two years. Bivariate and multivariate logistic regression was applied to identify associations and predictors. Findings – The results showed that the use of maternal health services was 50.8%. Adjusting for all other factors in the final model, age group 25–30 years (AOR: 2.30; 95% CI: 1.199–4.422), spouse communication (AOR: 7.31; 95% CI: 2.574–20.791), high accessibility (AOR: 2.552, 95% CI: 1.402–4.643) and high affordability (AOR: 10.89; 95% CI: 4.66–25.445) were significant predictors. Research limitations/implications – This is a community-based cross-sectional study, and hence cannot establish causal relationships. The research was conducted in a limited rural area mid-Western Nepal, and this may limit the generalization of results to other settings of the country. Practical implications – This research supports to local level government and district health authority to develop and implement need based action to increase maternal health service in the local context. Originality/value – Underutilization of maternal health services is the result of socioeconomic dynamics, poor access to health services and other physical developments. To increase utilization of maternal health services in rural areas, there is a need to tackle the root cause of health inequality such as reducing poverty, increasing female education, involving women in employment and increasing access to health as a priority development agenda by government authorities. This research supports local level government and district health authorities to develop and implement needs-based action to increase MHS in the local context.